2017
DOI: 10.1016/j.jaip.2017.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Virtual Teach-To-Goal™ Inhaler Technique Learning Module: A Mixed Methods Approach

Abstract: Background Most hospitalized patients with asthma or chronic obstructive pulmonary disease (COPD) misuse respiratory inhalers. An in-person educational strategy, teach-to-goal (TTG), improves inpatients’ inhaler technique. Objective To develop an effective, portable education intervention that remains accessible to hospitalized patients post-discharge for reinforcement of proper inhaler technique. Methods A mixed methods approach at an urban academic hospital was used to iteratively develop, modify and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…10,23 Screenshots of the V-TTG intervention were also published previously (eFigure 2 in Supplement 2). 24,25 Participants assigned to V-TTG were provided with a tablet device to complete the intervention, which consisted of self-assessment questions before demonstration, narrated video demonstration of correct technique, and self-assessment questions after demonstration; cycles of the narrated demonstration and self-assessment questions were repeated, as needed, until all questions were answered correctly or 3 rounds were completed. 10,23…”
Section: Intervention V-ttg Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,23 Screenshots of the V-TTG intervention were also published previously (eFigure 2 in Supplement 2). 24,25 Participants assigned to V-TTG were provided with a tablet device to complete the intervention, which consisted of self-assessment questions before demonstration, narrated video demonstration of correct technique, and self-assessment questions after demonstration; cycles of the narrated demonstration and self-assessment questions were repeated, as needed, until all questions were answered correctly or 3 rounds were completed. 10,23…”
Section: Intervention V-ttg Interventionmentioning
confidence: 99%
“…A direct-to-patient, technology-based intervention designed to be a low-cost, feasible solution was developed by members of our team at the University of Chicago, some of whom are authors on this report; this intervention is housed and licensed on the Smart Sparrow platform. 24,25 However, it is unknown whether this virtual educational intervention is as effective as in-person education. Our primary objective was to test whether this virtual intervention was as effective as in-person education for improving inhaler technique among patients hospitalized with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the recent Coronavirus (COVIT-19) pandemic has accelerated the use of Tele-Medicine as lockdowns and mandates meant that families and staff were less keen on face to face clinical meetings unless they were absolutely essential. While we believe face-to-face training is optimal it has been reported that inhaler instruction using the Teach-to-goal/Teach back technique is eminently possible via remote video consultation ( 28 ). Our SADCP therefore would lend itself to hybrid approaches with perhaps the first clinical assessment being face-to-face followed by some video consultations.…”
Section: Limitationsmentioning
confidence: 90%
“…Participants were asked to read the row of words from left-to-right when measuring visual acuity in the right eye and right-to-left when measuring visual acuity in the left eye starting with the largest font first. Data were collected and managed using REDCap version 11.1.7 (Vanderbilt University) [ 12 ].…”
Section: Methodsmentioning
confidence: 99%